Triwaca dan Literacycloud: Ragam Membaca Menyenangkan selama Pandemi Virus Corona - Kisno Kisno; Mega Romauly Tampubolon; Calen Calen; Angel Talenta Marpaung; Victor Marudut Mulia Siregar; Sarida Sirait (Universitas Muhammadiyah Semarang, 2021)
The outbreak of Corona virus pandemic is changing the face of the education process in various parts of the world. Lots of the educational processes are transformed into online or learning from home. In spite of this, it was found that some teachers experienced difficulties administering online teaching. This phenomenon moves the community service team to organize a varied, interactive, and fun learning process for educators at the elementary school level in Deli Serdang Regency, North Sumatra. A total of 90 educators from private and state schools were trained to use a fun reading style using the Literacycloud browser. The training began with online dissemination, followed by visitations to target schools. All educators were asked to practice Triwaca, namely Uninterrupted Sustained Silent Reading (USSR), story pyramids, and BookTalk. performance. The results of cognitive measurements showed an increase in educators' knowledge about the pleasuring reading by 50%. In addition, the target school has produced more than 20 story pyramids and practicing BookTalk both online and offline for students. In conclusion, the Triwaca and Literacycloud programs in general ran successfully as seen from the program achievement indicators.